(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Morphological study of some non conventional oil seeds are of great interest for the development of some communities. In this investigation, shea kernels from 4 localities in Chad were studied. The sun dried shea kernels from Beinamar locality had the greatest length (28.30 ±3,25 mm), diameter (20.58 ±2.46 mm), weight (5.56 ±1.52 g) and moisture content (3.79 ± 0.14 %), whereas the kernels of Penie village had the least values (24.25 ± 2.54, 19.02 ± 2.34, 4. 0 ± 1.01 and 3.54 ± 0.33 respectively) of the mentioned characteristics. On the other hand, the total lipid content of Penie’s shea kernels was the highest (58.5%) whereas that of Bolo village was the lowest one (53.53 ± 0.40 %). The acid value of the 4 samples was extremely high (25.31 ± 0.71- 38.30 ± 0.76 mg KOH/g oil), whereas the acid value of the oven dried shea kernels produced using boiling method was low (1.2 - 2.1). The kinetics of press extraction of shea butter suggested that the extraction time is 12 min.